2015
DOI: 10.1149/2.0211514jes
|View full text |Cite|
|
Sign up to set email alerts
|

Review—Electromobility: Batteries or Fuel Cells?

Abstract: This study provides an analysis of the technological barriers for all-electric vehicles, either based on batteries (BEVs) or on H 2 -powered proton exchange membrane (PEM) fuel cells (FCEVs). After an initial comparison of the two technologies, we examine the likely limits for lithium ion batteries for BEV applications, and compare the projected cell-and system-level energy densities with those which could be expected from lithium-air and lithium-sulfur batteries. Subsequently, we will review the current devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
367
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(396 citation statements)
references
References 151 publications
6
367
2
2
Order By: Relevance
“…45 Upon conversion of these figures into mass-specific ORR activities (Fig. 6B), Pt 3 Ni and Pt 1.5 Ni reach the DOE ORR activity target at 0.95 V RHE that was extrapolated from the reported value 21 of 440 A/g Pt at 0.9 V RHE assuming a Tafel slope of 60 mV dec −1 consistent with our measurements (cf. Fig.…”
Section: Resultssupporting
confidence: 86%
“…45 Upon conversion of these figures into mass-specific ORR activities (Fig. 6B), Pt 3 Ni and Pt 1.5 Ni reach the DOE ORR activity target at 0.95 V RHE that was extrapolated from the reported value 21 of 440 A/g Pt at 0.9 V RHE assuming a Tafel slope of 60 mV dec −1 consistent with our measurements (cf. Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recently, several studies have identified that the attainment of areal capacities as high as 4-8 mAh/cm 2 while minimizing the electrolyte content are the key factors in meeting these requirements. [1][2][3] The only currently commercialized Li-S battery has a significantly lower areal capacity of 2.5 mAh/cm 2 and operates in the presence of excess electrolyte, 4 necessitating significant technological breakthroughs to facilitate the possible use of Li-S batteries in the transportation sector. One of the main barriers to achieving such breakthroughs is the lack of fundamental understanding of the mechanism behind the operation of Li-S batteries.…”
mentioning
confidence: 99%
“…These developments are underway and have made significant progress. 5 Cost however is also closely tied to power density of the fuel cell stack. It is obvious that with higher power density less cells or an accordingly smaller cell area with the related reduced material use, is leading to a cost reduction if the high power density materials are of comparable cost.…”
mentioning
confidence: 99%